AI Adoption in the Enterprise 2021 - Loukides, Michael Kosta (O'Reilly Media, Inc., 2021)
There's no question: more people are using AI than ever before, and companies across industries are striving to get AI projects up and running. But how many have actually put revenue-bearing products into production? And how does your own organization measure up? In this new report, Mike Loukides, O'Reilly's vice president of content strategy, shares the results of a recent survey on how companies are adopting AI. You'll learn how (and where) AI use has grown over the past year, the significant barriers that remain, and the techniques and tools developers are--or should be--using for their applications.